Some Formal and Stylistic Characteristics of a Ghazel in Persian by Ahmad Rushdi Mostari - Karahalilović, Namir (Prilozi za orijentalnu filologiju, 2017)
Ahmad Rushdi Mostari is one of the Bosniak authors who wrote in Oriental languages. His diwan of poetry in Turkish has been preserved, but he also wrote in the Persian language. This paper presents one Rushdi’s ghazel in Persian, unknown to the general public to date, with the analysis of some of its formal and style characteristics. Through the adequate selection at the lexical level, the author achieves the meaning and polyvalence of the poem, leaving space for its versatile reception and interpretation. At the formal level, the ghazel is characterised by the inconsistent use of the word radīf, a versification element immanent to Persian poetry since its earliest time. Without a possibility of a definitive confirmation of that attitude – until it has been checked on a comprehensive poetic corpus – we can assume that such a procedure reflects the author's aspiration to critical reconsideration of formal poetic rules. Particular value is added to the poem by the author's extensive skill in building various style-figures (metaphors, comparisons, cumulations, rhetoric switches and antitheses), which he subtly nuances and uses masterly.